Spinoza on Ethics and Understanding - Winch, Peter (Anthem studies in Wittgenstein, 2020)
This volume collects together Peter Winch's previously unpublished lectures on the philosophy of Baruch Spinoza. Winch's original interpretation of Spinoza's Ethics sheds new light on the work of one history's most difficult and admired philosophers from a different perspective.